PERBEDAAN DAN HUBUNGAN TERHADAP EFISIENSI DIRI DAN KARAKTER DISIPLIN SISWA SMA - Azadboni, Fatemeh Khodadadi; Septi, Sabila Eka (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
Currently, students' self-efficacy and discipline are very important, especially at the high school level to help students improve their learning abilities. This study aims to answer the research question, namely how the results of descriptive statistics on self-efficacy variables and the disciplinary character of high school students in physics subjects. Are there differences and relationships between self-efficacy and the disciplinary character of physics high school students? The method used in this study is a mixed method. The research results are based on the t test which states that the comparative data is smaller than 0.05 and the correlation test which states the data results are smaller than 0.05. The conclusion of this study is the difference and relationship between self-efficacy and character discipline of students at Senior high school 5 Jambi City and Alberta High School Diploma in physics subjects. The update of this research is that knowing the relationship between self-efficacy and disciplinary character can be used as a source of good research in the future and for teachers and schools at the high school level. This research is limited by high school level and physics subjects.